The problem of women who are abused in couple relations - Vega Gonzáles, José (1998)
Trough the present study we analyze the problems inserted in the situations of domestic violence, couple violence and against women in general, inquiring causes and reasons why happen these facts in our culture. The analysis includes details refereed to the sequence of starting and developments of the behaviors of mistreat in the persons by means of social learning. Alternatives are proposed for the solution of the conflicts based on the experiences extracted of other countries in Latin America and Caribe. It is emphasized specially that any type of prescriptions to be used should consider integral aspects, due to multiple factors that influence the violent episodes.